T-Cell Activation: Post-Infection Diagnostic Tool for COVID-19 - Simara, P; Tesarova, L; Tapuchova, I; Celerova, J; Koutna, I (Folia biologica, 2021)
COVID-19 is caused by the SARS-CoV-2 virus and has spread globally in 2020. Cellular immunity may serve as an important functional marker of the disease, especially in the asymptomatic cases. Blood samples were collected from 46 convalescent donors with a history of COVID-19 and 38 control donors. Quantification of the T-cell response upon contact with SARS-CoV-2 proteins in vitro was based on IFN-γ. Significantly higher numbers of activated cells were measured in patients who underwent COVID-19. Anti-SARS-CoV-2 T cells were detected weeks after the active virus disappeared from the organism. Repeated sample collection after five months proved that the T-cell activation was weaker in time in 79 % of the patients. In the majority of cases, the CD4+ helper T-cell subpopulation was responsible for the immune reaction. Moreover, different viral proteins triggered activation in CD4+ helper and in CD8+ cytotoxic T cells. Together, these findings suggest that the T-cell activation level identifies the individuals who underwent COVID-19 and may become a diagnostic tool for the disease.
Keywords: T-lymfocyty; aktivace lymfocytů; T-Lymphocytes; COVID-19; Antibodies, Viral; Humans; Lymphocyte Activation; lidé; SARS-CoV-2; protilátky virové